Analisis Reidentifikasi Empat Masalah Utama Koperasi di Kabupaten Subang sebagai Dasar Penyusunan Strategi - Hanny -; Kezia Kurniawati; Benny Shan F Waruwu; Rangga Pribadi (Universitas Kristen Maranatha, 2017)
Abstract A Cooperative is an autonomous association of persons with similar interest for providing and selling products then share the profits based on the contribution of each member (Hill and Hill 2005). According to Anak Agung Gede Puspayoga, the cooperatives in Indonesia haven’t contributed in Indonesian economy significantly, Their contributions was less than 2% to Gross Domestic Product although there were 209,000 units of cooperative in Indonesia (Ahsan and Nurmayanti 2016). The RPJMD 2013-2018 has identified 4 main issues that cooperatives face in Indonesia. The question is whether the same issues were happened in Subang or it only just some general issues in this country without concern about the particular issues in each region of Indonesia. Based on this phenomenon and question, this study presents about the analysis of the strategy and the re-identification of cooperative’s main issues in Subang. The sample was using purposive sampling method and obtained a sample of 30 cooperatives in Subang. The analysis data was performed with the descriptive statistics. The result of this study indicates that there are 3 of 4 main issues which identified by RPJMD, have been faced by the cooperatives in Subang and there are several strategies could be applied to solve the issues. Keywords: Cooperative; Four Main Issues; Re-Identification; Strategy